Peran Struktur Modal dalam Memediasi Profitabilitas Terhadap Nilai Perusahaan pada Sektor Basic Materials di BEI Periode 2019-2023 - Kristina Br. Purba, Angel; Sianturi , Jeudi A.T.P; Purba, Jon Henri (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The purpose of this study is to obtain empirical evidence of capital structure in mediating profitability on firm value. The sampling method in this study uses purposive sampling, namely companies classified as basic materials companies listed on the Indonesia Stock Exchange for the 2019-2023 period that have met the criteria are 45 companies. The software analysis used is WarpPLS version 8.0. The results of this study indicate that the profitability and liquidity variables directly have a positive effect on the value of the Company, the Company size variable does not affect the value of the Company. The profitability ratio has a positive effect on capital structure. The test results prove that the capital structure is able to mediate the effect of profitability on firm value.